2022
DOI: 10.7554/elife.78055
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic location is a determinant of the detrimental effects of α-synuclein pathology to glutamatergic transmission in the basolateral amygdala

Abstract: The presynaptic protein α-synuclein (αSyn) has been suggested to be involved in the pathogenesis of Parkinson’s disease (PD). In PD, the amygdala is prone to develop insoluble αSyn aggregates, and it has been suggested that circuit dysfunction involving the amygdala contributes to the psychiatric symptoms. Yet, how αSyn aggregates affect amygdala function is unknown. In this study, we examined αSyn in glutamatergic axon terminals and the impact of its aggregation on glutamatergic transmission in the basolatera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The difference in α-syn levels between the VGLUT1 positive terminals in amygdala and the VGLUT2 positive terminals in thalamus is further supported by reduced activity in cortico-amygdalal synapses in α-syn knockout mice [149]. Additionally, when α-syn aggregates, leaving a reduced amount of soluble α-syn, the transmission in VGLUT1 synapses in amygdala, but not the VGLUT2 synapses in thalamus, is reduced [149]. Although the general tendency is that more α-syn is present in VGLUT1 terminalis compared to VGLUT2 terminals, in some regions, like substantia nigra pars compacta, there are both α-syn positive and negative VGLUT1 synapses [150].…”
Section: The Role Of α-Syn In Glutamatergic Synapsesmentioning
confidence: 84%
See 2 more Smart Citations
“…The difference in α-syn levels between the VGLUT1 positive terminals in amygdala and the VGLUT2 positive terminals in thalamus is further supported by reduced activity in cortico-amygdalal synapses in α-syn knockout mice [149]. Additionally, when α-syn aggregates, leaving a reduced amount of soluble α-syn, the transmission in VGLUT1 synapses in amygdala, but not the VGLUT2 synapses in thalamus, is reduced [149]. Although the general tendency is that more α-syn is present in VGLUT1 terminalis compared to VGLUT2 terminals, in some regions, like substantia nigra pars compacta, there are both α-syn positive and negative VGLUT1 synapses [150].…”
Section: The Role Of α-Syn In Glutamatergic Synapsesmentioning
confidence: 84%
“…There is also a distinction in the amount of α-syn between the vesicular glutamate transporter 1 (VGLUT1) positive terminals and VGLUT2 positive terminals. In, e.g., mouse amygdala, where most of the glutamatergic neurons are VGLUT1 positive, there is much more α-syn than in the VGLUT2 positive glutamatergic neurons in the mouse thalamus [149]. The difference in α-syn levels between the VGLUT1 positive terminals in amygdala and the VGLUT2 positive terminals in thalamus is further supported by reduced activity in cortico-amygdalal synapses in α-syn knockout mice [149].…”
Section: The Role Of α-Syn In Glutamatergic Synapsesmentioning
confidence: 98%
See 1 more Smart Citation
“…Microglial engulfment may not be the sole cause of synapse degeneration during α-synuclein propagation. Other studies have suggested that PFF also impacts the formation and molecular organization of presynaptic terminals by inhibiting β-neurexin [ 34 ] or by decreasing the levels of soluble α-synuclein [ 35 ]. However, it is worth noting that the latter studies examined the direct effects of PFFs on neurons in culture, whereas our study assessed the effects of α-synuclein propagation throughout a neural network in an intact-tissue environment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CD3+ T cells were also identified in the hippocampus, near Lewy bodies and the excitatory presynaptic marker vesicular glutamate transporter 1 (vGLUT1) [ 50 ]. Previous studies have demonstrated co-localisation of α-syn and vGLUT1+ neurons in the hippocampus of C57BL/6N mice [ 51 , 52 ] and it has been proposed that vGLUT1+ neurons are vulnerable to α-syn pathology, resulting in detrimental effects on synaptic transmission [ 53 ]. Increased immunoreactivity for the pro-inflammatory cytokine interleukin 17A (IL-17A) has been detected in DLB/PDD brains [ 50 ], implying that Th17 cells that express this cytokine may contribute to neuronal damage.…”
Section: T Cells In Dlbmentioning
confidence: 99%